Características histoquímicas e estruturais do testículo do morcego hematófago (Desmodus rotundus rotundus, Geoffrey, 1810). - Orsi, A. M.; Vicentini, Carlos Alberto [UNESP]; Dias, S. M.; Michelin, S. C.; Viotto, M. J. (My University, 1990)
The testicular stroma of the vampire bat including the testicular capsula and the lamina propria of the seminiferous tubuli, was strongly PAS-positive. This observation was a possible indication of great amounts of structural glycogen and other glycoconjugates at the level of smooth muscle cells; elongated contractile cells and/or collagen frameworks of the tunica albuginea and tubular lamina propria. In the last the basement membranes of the seminiferous tubules were particularly strongly PAS positive, as an indication of their neutral mucosubstances structural composition, previously described (Malmi et al., 1987). The epithelium lining from the cavitary and surface rete testis complex showed low reactivities to mucosubstances; total proteins and lipids and oxidative enzymes studied. Although the apical granulation at the rete testis epithelium showed an intense PAS reactivity with hypothesis of glycoprotein secretion, through the rete. The PAS, Sudan Black B, NADH, MDH and LDH reactions of the testicular interstitium seem correlate to steroid metabolism (biosynthesis and secretion), at the Leydig cells level. The seminiferous epithelium generally had low reactions to all the histochemical studies realized. Particularly in the adbasal compartment the histochemical localizations of NADH diaphorase and LDH were possible related to glycolytic activities and general carbohydrates metabolism, both enzymes, and hydrogen transport, the NADH. The strong PAS, diastase and PAS, and alcian blue pH 2.5 and PAS reactions observed in the adluminal seminiferous epithelium compartment were directly related to the spermatids acrosomal glycoconjugates structuration. Also the SDH localization at this level seems to be related to the mitochondrial activities at the middle piece level in the late spermatids.
Histochemical and structural characteristics of the testis of the vampire bat (Desmodus rotundus rotundus, Geoffrey, 1810)
Keywords: dihydrolipoamide dehydrogenase; glycoconjugate; lactate dehydrogenase; malate dehydrogenase; succinate dehydrogenase; animal; bat; histology; male; metabolism; microtomy; periodic acid Schiff stain; testis; Animal; Chiroptera; English Abstract; Glycoconjugates; Lactate Dehydrogenase; Lipoamide Dehydrogenase; Malate Dehydrogenase; Male; Microtomy; Periodic Acid-Schiff Reaction; Succinate Dehydrogenase; Support, Non-U.S. Gov't; Testis